Growth Differentiation Factor 15 Protects SH-SY5Y Cells From Rotenone-Induced Toxicity by Suppressing Mitochondrial Apoptosis - Li, Peizheng; Lv, Hongbo; Zhang, Bohan; Duan, Ruonan; Zhang, Xiufang; Lin, Pengfei; Song, Chengyuan; Liu, Yiming (Frontiers in Aging Neuroscience, 2022)
Objective: Parkinson's disease (PD) is the second most common neurodegenerative disorder worldwide. Ther are proofs suggest that mitochondrial dysfunction should be suspected as one of pathogenesis in PD. Growth/Differentiation Factor-15 (GDF15) has been reported impacting mitochondrial function in PD. However, the relation between mitochondrial function and GDF15 induction has not been explained well. Hence, we aim to reveal the effect of GDF15 induction in SH-SY5Y cells with rotenone toxicity, a cell model of PD. Methods: SH-SY5Y cells were exposed to 1 μM rotenone as PD models. Cells were transfected with GDF15 overexpression plasmid and empty vector. We analyze the expression level of GDF15, BCL-2/BAX, P53, PGC1-α, α-syn and TH in GDF15 overexpressed cells by western blottingting, enzyme-linked immunosorbent assay (ELISA), and quantitative real-time polymerase chain reaction (qRT-PCR). Cytotoxicity of rotenone was measured by CCK-8 assay. Cell apoptosis was detected by ﬂow cytometry and TUNEL assay. The effect of GDF15 on oxidative stress and mitochondrial function was revealed using DCFH-DA, mito-SOX, JC-10 assay and Seahorse XF Cell Mito Stress Test. Results: GDF15 protected rotenone treated SH-SY5Y cells from rotenone-induced toxicity by preserving mitochondrial function and decreasing apoptosis in which GDF15 might via influencing PGC1α by regulating p53. In addition, GDF15 overexpression could improve Akt and mTOR phosphorylation, leading to activate PI3K/Akt/mTOR pathway. However, these protective effects were eliminated when cells were treated with PI3K/Akt specific inhibitor, LY294002. Conclusions: Our findings suggest that GDF15 can protect mitochondrial function and inhibit apoptosis in SH-SY5Y cells after exposing to rotenone by upregulating PGC1α via p53. These effects might act by its anti-apoptotic effects mediated by the PI3K/Akt/mTOR signaling pathway.